Critical thinking, metacognitive skills, and cognitive learning outcomes: a correlation study in genetic studies - Miharja, Fuad Jaya; Hindun, Iin; Fauzi, Ahmad (Biosfer: Jurnal Pendidikan Biologi, 2019)
Understanding the concept of genetics needs to be balanced with high-level thinking skills and excellent metacognitive skills. However, efforts to measure the correlation between these two factors are still carried out partially. This study aims to determine the correlation between critical thinking, metacognitive skills, and cognitive learning outcomes in genetic studies. This study is correlational that measures the relationship between variables students’ critical thinking skills (X1), metacognitive skills (X2), and students’ cognitive learning outcomes (Y). As much as 118 students who took the genetic course were involved as the population as well as research subjects. Data collection instruments in this study consisted of tests of critical thinking skills and metacognitive skills tests as well as students' cognitive assessment sheets. The results showed that the achievement of student cognitive learning outcomes was influenced by 94% of the dependent variables examined in this study, while other variables influenced the remaining 6%. The conclusion of this study recommends that the regression models and coefficients used in this regression can be used to predict cognitive learning outcomes.